The Effectiveness of Reproductive and Sexual Health Education by Counselling and Small Group Discussion on Knowledge and Attitudes of Adolescents Aged 16-17 Years - Khotimah, Khusnul (HM Publisher, 2023)
Adolescents are in a phase of rapid growth and development physically, psychologically, intellectually, socially, and sexually. This gives rise to great curiosity and a tendency to take risks without consideration. This causes various consequences, including sexual transmitted diseases and unwanted pregnancies. This research aims to explain the effectiveness of reproductive and sexual health education using counselling and small group discussion methods on adolescents' level of knowledge and attitudes. This research is a quasi-experimental study with two treatment groups and one control group. A total of 154 teenagers from 556 respondents were involved using the proportional random sampling method. Each treatment group was treated with different learning methods, namely the lecture and small group discussion methods, totaling 154 respondents. Data was collected using a before and after questionnaire, then analyzed using the Wilcoxon Signed Rank Test and Mann Whitney Test with a significance level of p<0.005. The results of the research show that the effectiveness of the lecture method and small group discussion is: 1) knowledge about the small group discussion method and the lecture method have the same significance value p=0.000 (<0.05), 2) attitudes towards the behavior of the counselling method are significantly different compared to small group discussion p=0.000 (<0.05). In conclusion, small group discussion method is better used to increase knowledge and attitudes towards sexual and reproductive health behavior in adolescents.